2016
DOI: 10.1016/j.carbon.2015.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Assessing carbon nanotube arrangement in polystyrene matrix by magnetic susceptibility measurements

Abstract: Multi-wall carbon nanotubes filled with iron nanoparticles were combined with polystyrene to evaluate interface interactions and nanotube orientation in composite using magnetic susceptibility measurements. Iron-containing species were introduced into MWCNT cavities as the result of catalytic chemical vapor deposition synthesis using ferrocene as a catalyst source. Polystyrene loaded with certain quantity of MWCNTs was uniaxially stretched to provide the nanotube alignment. Magnetic susceptibility measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Advancements are being made to produce such nanocomposites; however, the challenges in the characterization of alignment of CNTS and matrix are ominous and complicated due to non-crystallinity of the materials, the elemental identity of the filler, and the hindrance from matrix prevents the use of diffraction and spectroscopic methods. Makarova et al came up with novel magnetic susceptibility measurements that offer critical insights pertaining to the orientation of CNTs and PS molecules [99]. The ability to make such measurements was by incorporation of ironbased nanoparticles in the nanotube cavity that act as anisotropic magnetic species.…”
Section: Polystyrene Cnt Nanocompositesmentioning
confidence: 99%
“…Advancements are being made to produce such nanocomposites; however, the challenges in the characterization of alignment of CNTS and matrix are ominous and complicated due to non-crystallinity of the materials, the elemental identity of the filler, and the hindrance from matrix prevents the use of diffraction and spectroscopic methods. Makarova et al came up with novel magnetic susceptibility measurements that offer critical insights pertaining to the orientation of CNTs and PS molecules [99]. The ability to make such measurements was by incorporation of ironbased nanoparticles in the nanotube cavity that act as anisotropic magnetic species.…”
Section: Polystyrene Cnt Nanocompositesmentioning
confidence: 99%
“…Before the solvent evaporation step, it is likely that PS block interacts favorably with CNT walls by π–π stacking, , while epoxidized polyisoprene (ePI) block extends free into solution due to the favorable interaction with DGEBA, as expected from the similar solubility parameters (δ ePI = 20.3 MPa –1/2 ; δ DGEBA = 20.7 MPa –1/2 ) . On the basis of the previous argument, Figure A depicts a possible conformation for eSIS consisting of PS blocks wrapping CNT walls and ePI subchains generating a steric barrier that prevents CNT agglomeration, in a similar way as previously reported by Kang and Taton for a polystyrene- block -poly­(acrylic acid) BCP surrounding single-walled carbon nanotubes dispersed in water .…”
Section: Results and Discussionmentioning
confidence: 76%
“…In this regard, AFM phase imaging revealed that epoxy/eSIS films prepared with toluene as solvent (without DT) results in smaller sphere-like nanostructures (Supporting Information), while when using DT as cosolvent the BCP renders short cylinder-like nanostructures, presumably due to the higher mobility of eSIS during the self-assembly stage (before the solvent evaporation step under vacuum) enabling nanodomain association/aggregation. Before the solvent evaporation step, it is likely that PS block interacts favorably with CNT walls by π−π stacking, 50,51 while epoxidized polyisoprene (ePI) block extends free into solution due to the favorable interaction with DGEBA, as expected from the similar solubility parameters (δ ePI = 20.3 MPa −1/2 ; δ DGEBA = 20.7 MPa −1/2 ). 18 On the basis of the previous argument, Figure 3A depicts a possible conformation for eSIS consisting of PS blocks wrapping CNT walls and ePI subchains generating a steric barrier that prevents CNT agglomeration, in a similar way as previously reported by Kang and Taton for a polystyreneblock-poly(acrylic acid) BCP surrounding single-walled carbon nanotubes dispersed in water.…”
Section: ■ Experimental Sectionmentioning
confidence: 96%
“…rings are aligned perpendicular to it [32]. When the polystyrene is filled with the carbon nanotubes, its diamagnetic response changes not only quantitatively but also qualitatively.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%